Quem da pátria sai a si mesmo escapa?: um estudo psicanalítico sobre um caso de migração - Escobari, Daniela (2008)
The problems surrounding migration include psychotic surges, depression, alcoholism, adaptation disorders, stress which are discussed in multiple studies, making clear the importance of the issue for mental health. It is broadly agreed, that migration has clear implications for the individual, her family, her community, and the nation as a whole. Listening to patients in clinical settings, showed that suffering associated with migration had as undercurrents stories of how these individuals were psychologically built-up. We raise the hypothesis that migration in some cases could be an exit attempt from certain psychological impasses. Our objective therefore became to identify and investigate the origins and vicissitudes of this kind of psychological movement that we found in the geographical dislocation of certain subjects. This psychoanalytical study, within the field of fundamental psychopathology, allowed us to identify a movement we called an attempt of parental (re)construction. From the clinical case, we were able to formulate three streams of parental (re)construction: Migration and Foreignness / paternal (re)construction, Migration as the space in between and Migration and the second mirror / maternal (re)construction